Ehrlichia spp. infection in domestic cats from Rio de Janeiro State, southeast Brazil - Guimarães, Andresa; Raimundo, Juliana Macedo; Rodrigues, Raisa Braul; Peixoto, Maristela Peckle; Santos, Huarrisson Azevedo; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP]; Baldani, Cristiane Divan (FapUNIFESP (SciELO), 2019)
Ehrlichiosis is caused by agents belonging to Ehrlichia genus. Despite the frequent reports on the serological and molecular detection of E. canis in dogs in Brazil, there is scant data on ehrlichiosis in brazilian cats. This study aimed at investigating the occurrence of Ehrlichia spp. in domestic cats from Greater Rio de Janeiro, and evaluating hematological changes associated with this rickettsial infection. We searched for IgG antibodies against E. canis on blood samples of 216 cats by Indirect Fluorescence Assay (IFA). Additionally, we performed nested PCR (nPCR) and real-time PCR (qPCR) assays targeting E. canis-16S rRNA and dsb gene, respectively. Fifty-seven (26.4%) cats were seropositive for Ehrlichia spp. by IFA. Ehrlichia spp.-16S rRNA gene fragments were detected in 3 cats (1.4%). Although the obtained 16S rRNA sequences showed 99 to 100% identity with E. canis, cats were negative in qPCR. Anemia, thrombocytopenia, leukocytosis, left shift neutrophil and hyperproteinemia were observed. Anemia was statistically associated with seropositivity to E. canis and kittens showed lower positivity rates (p<0.05). This study showed that Ehrlichia spp. occur in domestic cats from Greater Rio de Janeiro. Further studies involving culture isolation are much needed to more precisely characterize these organisms.
Infecção de Ehrlichia spp. em gatos domésticos da Grande Rio de Janeiro, sudeste do Brasil
Keywords: Ehrlichiosis; Feline; Hematology; IFA; Nested PCR